Assédio moral e autocuidado no trabalho de assistência a vítimas de violência contra a mulher - Santos, Karine David Andrade (2018)
The activity of assisting victims of violence against women raises a range of emotions in the workers in this area whose consequences may lead to the reproduction of the violent relations assisted through the bullying between the members of the team and the illness at the individual and group levels. To minimize these impacts and preserve the health of these professionals, self-care is pointed out as a fundamental tool for this purpose. Thus, the present investigation addresses workplace harassment and the health of professionals in the care of victims of violence against women, an attempt that was extended in describing the practices of bullying at work, portraying the experience of serving women victims of violence. violence and observe the self-care practices exercised by participants at personal, professional, collective and institutional levels. To achieve these objectives, seven chapters have been developed in the form of articles.Thus, Chapter 1 undertook a conceptual analysis on workplace harassment, self-care and discussed the vulnerability of these professionals promoted by the State based on neoliberal economic bases. In Chapter 2, a systematic review on illness and self-care was developed in professionals assisting victims of violence through the search of these themes in three databases: IndexPsi, Scielo and PsycInfo. After applying the inclusion and exclusion criteria, 41 articles were collected for analysis, whose results point to the need for productions directed at the factors that facilitate and hinder the care of these professionals. Chapter 3 had the objective of verifying self-care practices at the individual, group, collective and institutional levels carried out by professionals of assistance to victims of violence against women. To that end, twelve professionals (two educators, five social workers, three psychologists and two lawyers) from four centers of assistance to victims of violence against women in the city of Aracaju and in the interior of Sergipe were submitted to an interview script with questions about the aspects in question. Through the use of the Iramuteq software, the findings pointed to the limitation of individual self-care to family spaces, obstacles to physical health care and absence of participants, and insufficient self-care in the institutional setting. Also with this same public, methods of study and with the use of content analysis, the chapter 4 was elaborated that aimed to describe the moral harassment in the work experienced by professionals of assistance to victims of violence against women. The data indicated that the participants are subject to devaluation, defamation and intimidation that materialize in specific situations of their work activities by the hierarchical superiors causing consequences for the physical, mental health and, mainly, the motivation for the work of the harassed ones. This production revealed the importance of implementing preventive and intervention strategies aimed at bullying in these workspaces. Chapter 5, which was also carried out with the same participants, methods and the use of the Iramuteq software, aimed to describe the working conditions, to investigate the experience of attending to women victims of violence and to observe the self-care practices practiced by the professional group at the personal, professional, collective and institutional levels. The results provided a framework for exposure to violent conflicts and working relationships, poor working conditions, a personalistic institutional dynamics and difficulties for follow-up and follow-up of the cases served. These findings reinforce the need to strengthen the public policy system. In turn, Chapter 6 was built with the same objective as the previous section and was implemented through the application of an interview script with 10 professionals of assistance to victims of violence against women from public and private associations in Spain whose information was collected analyzed by the computer method Iramuteq. In this investigation, the researchers were found to be exposed to precarious working conditions, signs of illness due to the approximation to the reality served and the efforts of personal self-care through individual psychotherapy, an insufficiency and lack of institutional self-care and evidence of the presence of relationships violent at work. Finally, Chapter 7 was elaborated through a comparison between the results extracted from the researches carried out between Brazil and Spain whose notes are directed towards similarities in relation to subjective experience and a distancing in the characteristics of self-care undertaken by Brazilian and Spanish professionals.These results point to the importance of effective self - care programs and the preparation of proposals to take care of the professional team that takes into account the social, economic and cultural characteristics of the intervention sites.